Gulf War and health depleted uranium, sarin, pyridostigmine bromide, vaccines - Fulco, Carolyn; Liverman, Catharyn T.; Sox, Harold C. (National Academies Press, 2000)
The men and women who served in the Gulf War theater were potentially exposed to a wide range of biological and chemical agents. Gulf War and Health: Volume 1 assesses the scientific literature concerning the association between these agents and the adverse health effects currently experienced by a large number of veterans